Development of an Online Counseling Model Based on Mindfulness-Based Cognitive Therapy to Reduce Alexithymia in Students - Mulia, Fika Dwi; Ardi, Zadrian (Universitas Negeri Padang, 2024)
The instability of psychological development during this period puts teenagers at risk of experiencing alexithymia, which is a disorder in the form of an inability to identify, understand and respond to the feelings of themselves and others which then appears in the form of weak empathy. A further impact of this disorder is interpersonal relationship problems at the next stage of adolescent development. Apart from that, there is a tendency for more serious mental disorders to emerge. The aim of this research is to develop an online counseling model based on Mindfulness-based Cognitive Therapy to reduce the condition of alexithymia experienced by middle school students. The model developed is predicted to be able to provide significant changes considering that counseling media is also carried out via a web-based platform, so that it will increase the opportunity to reduce mental disorders experienced by students. This research is development research which is planned to last for 1 (one) year, where the results of research that has been carried out previously, especially related to online counseling (since 2014) are the basis of this research. This research uses a research and development approach with modified ADDIE principles, resulting in a product in the form of an online counseling model that is able to accommodate the process of reducing alexithymia disorders in students. With a combination of a post-modern counseling approach and the use of internet media, it produces a product that has high novelty in reducing psychological disorders in students.